Electrochemical study of symmetrical intermediate temperature - solid oxide fuel cells based on La0.6Sr0.4MnO3 / Ce0.9Gd0.1O1.95 for operation in direct methane / air. (20th March 2022) - Sanna, Caterina; Squizzato, Enrico; Costamagna, Paola; Holtappels, Peter; Glisenti, Antonella
Abstract: La0.6 Sr0.4 MnO3 (LSM), which is considered a state-of-the-art solid oxide fuel cell (SOFC) cathode, is investigated for application as an anode in direct methane intermediate temperature - solid oxide fuel cells (IT-SOFCs). Ce0.9 Gd0.1 O1.95 (CGO) is used as the electrolyte. The characterized electrode is a composite LSM/CGO, prepared in two different configurations: LSM crushed electrospun nanofibers / GDC powders, and LSM powders / GDC powders. The electrodes are tested in both air and direct methane conditions. At 815 °C, the polarization resistance Rp  = 1.6 Ωcm 2 in air, and Rp  = 0.15 Ωcm 2 in methane. Since perovskite-type manganites may show poor stability in reducing atmosphere, electrode stability is investigated. It is found that LSM shows a reversible modification of the crystal structure, assuming a Ruddlesden-Popper (RP) structure when exposed to methane. The RP structure is expected to be more stable compared to the LSM single perovskite. Furthermore, the composite electrode is expected to benefit from the presence of CGO, which is stable in reducing conditions.